Synthesis of nanoscale zero-valent iron doped carbonized zeolitic imidazolate framework-8 for methylene blue removal in water - Chen Shuai; Qiao Lemeng; Feng Xuejiao; Huang Yufu; Gao Guilan; Guan Jie; Lin Donghai (Polish Journal of Chemical Technology, 2023)
Nanoscale zero-valent iron-doped carbonized zeolitic imidazolate framework-8 (nZVI/CZIF-8) was prepared by carbonation of ferric nitrate and ZIF-8 at 800 °C and used as an adsorbent to remove methylene blue (MB) from water. The synthesized nZVI/CZIF-8 has a specific surface area of 806.9 m2/g, a pore volume of 0.86 cm3/g and an nZVI content of 1.35%, respectively. Both the nZVI/CZIF-8 and CZIF-8 have identical functional groups of O-H, C-H and C=C. With the increase of CZIF-8 size, MB removal rate increased. The doping of nZVI increased the MB removal percentage from 74.5% for ZIF-8 to 96.2% within 80 min for nZVI/CZIF-8. The MB removal percentage increased with the dosage of nZVI/CZIF-8. The MB adsorption with the adsorbents conforms to the Freundlich adsorption isothermal model and the removal rate fitted well to a pseudo-first-order model. The results demonstrate the feasibility of synthesizing high active and stable nZVI/CZIF-8 particles.